Dampak Penggunaan Tusuk Gigi terhadap Status Kesehatan Gingiva pada Masyarakat Dusun Siduntung Kabupaten Wajo - Rezki Dirman; Sandra, Eva Novianti; Asnuddin; Sakinah, Sri (Media Kesehatan Gigi : Politeknik Kesehatan Makassar, 2025)
A 2020 engineering report from the WHO states that periodontal disease affects almost 10% of the population worldwide. Meanwhile, the latest more specific data on periodontal disease from Riskesdes 2018 shows the prevalence of periodontitis at 74.1% in Indonesia. Periodontal disease is an inflammatory condition that occurs due to bacterial biofilms on the surface of the teeth, and is one of the main causes of tooth loss due to damage to periodontal tissue that cannot be healed. One of the things that often happens in daily life and has the potential to damage the gingival tissue is the use of toothpicks that are done roughly, too often, or not as recommended. The habit of using toothpicks to clean food residue between teeth is quite common. However, if a toothpick is used in the wrong way, especially one that has a rounded cross-section and does not fit the shape of the gums, it can cause mechanical injury to the gums. The purpose of the study was to determine the frequency of toothpick use affecting gingival health. The type of research uses quantitative descriptive, which is a type of research that uses directly reviewed field data to solve current problems. The research time is from June to July 2025. The research population was 100 people in Siduntung Hamlet. Sampling is known as sampling based on consideration. A sample of 30 respondents was taken, which was adjusted to inclusion and exclusion criteria. The results of a study in Siduntung Hamlet, Ongkoe Village, Belawa District, Wajo Regency show that the use of toothpicks has an impact on gingival health. The frequency of toothpick use is associated with the level of gingival inflammation, the more often it is used, the higher the risk of inflammation.